Adaptive proofs of knowledge in the random oracle model. Issue 6 (1st November 2016) - Bernhard, David; Fischlin, Marc; Warinschi, Bogdan
Abstract : The authors define a notion of adaptive proofs of knowledge (PoKs) in the random oracle model (ROM). These are proofs where the malicious prover can adaptively issue multiple statements and proofs, and where the extractor is supposed to extract a witness for each statement. They begin by studying the traditional notion of zero‐knowledge PoKs in the ROM and then show how to extend it to the case of adaptive adversaries and to simulation soundness, where the adversary can also learn simulated proofs. The authors' first main result is negative. Under common assumptions, they can show that the well‐known Fiat–Shamir–Schnorr proof system is not adaptively secure. As for the second result, they prove that an existing construction due to Fischlin (Crypto 2005) yields adaptively secure simulation‐sound PoKs in the ROM. Since the purpose of this work is to motivate and introduce adaptive proofs, they only briefly discuss some applications to other areas, for example that adaptive proofs seem to be exactly what one requires to construct chosen‐ciphertext attack‐secure public‐key encryption from indistinguishability under chosen plaintext attack secure schemes.